FusionSeq: a modular framework for finding gene fusions by analyzing paired-end RNA-sequencing data. - Sboner, Andrea.; Habegger, Lukas.; Pflueger, Dorothee.; Terry, Stephane.; Chen, David Z.; Rozowsky, Joel S.; Tewari, Ashutosh K.; Kitabayashi, Naoki.; Moss, Benjamin J.; Chee, Mark S.; Demichelis, Francesca.; Rubin, Mark A.; Gerstein, Mark B. (Tufts University. Tisch Library., 2019)
Abstract: We have developed FusionSeq to identify fusion transcripts from paired-end RNA-sequencing. FusionSeq includes filters to remove spurious candidate fusions with artifacts, such as misalignment or random pairing of transcript fragments, and it ranks candidates according to several statistics. It also has a module to identify exact sequences at breakpoint junctions. FusionSeq detected known and novel fusions in a specially sequenced calibration data set, including eight cancers with and without known rearrangements.; Keywords: Fusion Transcript, Junction Sequence, Chimeric Transcript, Fusion Junction, Transcript Fragment.; Springer Open.